Towards open science in Argentina: From experiences to public policies - Arza, Valeria (2017)
The emergence and wide diffusion of information and communication technologies created ever increasing opportunities for sharing and collaboration, which shortened geographic, disciplinary and expertise distances. There exist various technologies, tools and infrastructure that facilitate collaborative production processes in various social spheres, and scientific production is not an exception. Open science produces scientific knowledge in a collaborative way, including experts and non-experts and to share the outcomes of knowledge creation processes. We identify 68 open science initiatives in Argentina using different primary and secondary sources. This paper describes those experiences in terms of goals, disciplines and openness along research stages. Building on the relationship between characteristics of openness and expected benefits, we discuss policy implications in order to better support openness and collaboration in science.